Modelagem matemática de curvas tensão-deformação - Roney Eduardo Lino (2008)
Ti or other elements as, for instance, Nb or V, when added as microalloying elements, exert a retarding effect on the kinetics of static recrystallization, leading to pancaking of austenite when deformed at temperatures compatible to those in the finishing of commercial hot rolling mills. The effects of these additions on the kinetics of dynamic recrystalization is less known. This work proposes a model that will best represent the behavior of some steels in the hot deformation and assess whether the addition of microalloying elements would be able to alsodelay the kinetics of dynamic recrystallization It was adopted as a methodology in this work the study of the shape of the stress-strain curves obtained from isothermal hot torsion experiments. Analysis of the first and second derivative of the stress with respect to the strain when plotted against the stress gave clear evidence of the start and finish of dynamic recrystallization allowing the kinetics to be followed fully. Forthe modeling of stress-strain curves two models were used, one by Sellarsl which is already well known and disclosed in the literature, and an adaptation of Sellarss model where a model proposed by Jonas to monitor the dynamic recrystallization part was used. The results indicate that both proposed models represented well the behavior of materials inthe hot deformation. Similarly to the case of static recrystallization, dynamic recrystallization is also delayed significantly by the addition of microalloying elements. As a result, an assessment of the influence of each microalloying element at the beginning and end of the processof dynamic recrystallization could be here made.